Multiple Organ Injury (Liver, Spleen, Kidney) Following Blunt Abominal Trauma, Without Sign of Acute Abdomen - Gusti Ayu Agung Pritha Dewi; Putu Cahya Budi Utama (Greenation Publisher & Yayasan Global Research National, 2024)
Blunt abdominal trauma accounts for 80% of all abdominal trauma cases, with the liver, spleen, and kidneys being the most commonly affected organs. However, multiple organ injuries are rare, particularly in patients managed without surgical intervention. Case Report: A 52-year-old male presented to the Emergency Room (ER) with complaints of headache and left shoulder pain following a fall from a coconut tree. The mechanism of injury was unclear, and the patient denied abdominal pain. Initial investigations included brain MSCT, left shoulder X-ray, and laboratory tests. Brain MSCT findings were normal, while left shoulder dislocation was confirmed. The patient developed hemodynamic instability, prompting resuscitation, Focused Assessment with Sonography for Trauma (FAST), and laboratory evaluations. FAST revealed no intra-abdominal free fluid; however, laboratory results showed a decline in hemoglobin (Hb) levels. A contrast-enhanced abdominal CT scan was performed, revealing Grade II liver trauma (segment 5), Grade III splenic trauma (upper pole), and Grade IV right kidney trauma. The patient was managed conservatively with non-operative management (NOM) in the Intensive Care Unit (ICU). Results and Discussion: This case highlights the management of multiple abdominal organ injuries in the absence of overt clinical signs of blunt abdominal trauma. Initial FAST results were negative, with no evidence of intra-abdominal free fluid. In trauma patients with hemodynamic instability and an unclear source of bleeding, blunt abdominal trauma must remain a differential diagnosis. A contrast-enhanced CT scan, the gold standard for diagnosing intra-abdominal injuries, identified significant liver, spleen, and kidney trauma. Following stabilization with resuscitation, the patient was successfully managed with NOM. No signs of acute abdomen were observed during the hospital stay or at discharge. Conclusion: Contrast-enhanced CT scanning is essential for diagnosing high-risk intra-abdominal injuries in blunt abdominal trauma cases where FAST results are negative. It facilitates informed decision-making regarding conservative versus operative management and optimizes patient outcomes.